Air Pollution and Education Investment - Zhiming Cheng; Liwen Guo; Massimiliano Tani; Sarah Cook (Institute of Labor Economics (IZA), 2023)
Our study focuses on exploring the impact of air pollution on household investment in children's education in China. Air pollution poses a significant risk to some cities in northern China. We have used panel data from secondary schools in Shandong Province in 2017 and 2020 and discovered that a rise of one standard deviation of PM2.5 leads to a 9.6-44.6 percentage point decrease in the likelihood of parents spending on their children's education. The impact of air pollution on household education investment is mediated by parents' and children's educational expectations and household incomes. Our findings also indicate that high school students are more likely to receive higher education investment than middle school students, even at the same level of air pollution. The results of our study suggest that air pollution can lead to a decrease in human capital accumulation due to changes in parental behaviors induced by air pollution.
Keywords: Q53; I20; D10; 330; air pollution; education investment; China